Chediak-Higashi syndrome: case report in afro-descendant individual - Judde Lacerda Andrade Carlos; Márcio Vasconcelos Oliveira; Claudio Lima Souza (Sociedade Brasileira de Patologia Clínica, 2014)
This is a Chediak-Higashi Syndrome (CHS) case report in afro-descendant individual, male, 3 months old, born from consanguineous union. On admission he had fever for a month, unresolved pneumonia, and hepatosplenomegaly. He evolved to bacterial sepsis, septic shock, and death. CHS presents quantitative and morphological and hematological changes. Abnormal leukocyte inclusions are the pathognomonic finding of the disease; its recognition and differentiation from other leukocyte inclusions is essential for diagnosis and institution of therapy. Early diagnosis of CHS increases the life expectancy of the individual and provides appropriate therapeutic approach for patients affected by the disease.